CISD2-mediated mitochondrial dysfunction and iron redistribution contributes to ferroptosis in arsenic-induced nonalcoholic steatohepatitis - Jingyuan Zhang; Lu Wang; Yang Lu; Fei Zheng; Xiaoqian Ding; Xiaofeng Yao; Jie Bai; Ningning Wang; Guang Yang; Tianming Qiu; Xiance Sun (Ecotoxicology and Environmental Safety)
Arsenic in the environment, such as sodium arsenic (NaAsO2), is a frequently occurring hazard that has been linked to nonalcoholic steatohepatitis (NASH). Our prior research established the involvement of ferroptosis in arsenic-induced NASH, but the precise underlying mechanisms remain elusive. Here, we found that exposure to NaAsO2 had a suppressive effect on the expression of CDGSH iron-sulfur domain-containing protein 2 (CISD2) at the protein and gene levels, and overexpression of CISD2 inhibited NaAsO2-induced ferroptosis and NASH. Additionally, administration of NaAsO2 to hepatocytes triggered mitochondrial dysfunction, manifesting as the release of cytochrome c, impairment of the mitochondrial respiratory chain, and reduction in ATP synthesis. However, these adverse effects were alleviated through overexpression of CISD2. Intracellular iron redistribution was induced by overexpression of CISD2 and inhibited NaAsO2-induced ferroptosis. This inhibition was characterized by a reduction in cytoplasmic iron levels and an increase in mitochondrial iron levels. Our study demonstrated that NaAsO2 induced intracellular iron reorganization and mitochondrial dysfunction through CISD2 inhibition, leading to ferroptosis and NASH. This may provide a novel means of treatment of nonalcoholic fatty liver disease triggered by environmental factors.